Impact of outdoor environments on the quality of life - Eusuf, Muhammad Abu; Mohit, Mohammad Abdul; Sami Eusuf, Muhammad Mehbub R.; Ibrahim, Mansor (e-International Publishing House, Ltd., UK., 2018)
The characteristics of outdoor environment in urban spaces and morphology distress the quality of life (QoL) of urban dwellers and visitors. The main purpose of this study is to develop an extensive hypothesis on the parametric evaluation related to the adaptation of the urban environment and dweller’s QoL by methodical literature review, field observation and proposal on an alternative design strategy. The parameters include microclimate, urban space and traffic, waste management and other influencing factors are desired to envisage for effective investigation. Factors play a key role on the variation of QoL and instinctively affect the dwellers approach and comportment.